4α‐phorbol 12, 13‐didecanoate activates cultured mouse dorsal root ganglia neurons independently of TRPV4. (16th January 2013) - Alexander, R; Kerby, A; Aubdool, AA; Power, AR; Grover, S; Gentry, C; Grant, AD
<x xml:space="preserve">Abstract</x> Background and Purpose The Ca2+‐permeable cation channel TRPV4 is activated by mechanical disturbance of the cell membrane and is implicated in mechanical hyperalgesia. Nerve growth factor (NGF) is increased during inflammation and causes mechanical hyperalgesia. 4α‐phorbol 12, 13‐didecanoate (4αPDD) has been described as a selective TRPV4 agonist. We investigated NGF‐induced hyperalgesia in TRPV4 wild‐type (+/+) and knockout (–/–) mice, and the increases in [Ca2+]i produced by 4αPDD in cultured mouse dorsal root ganglia neurons following exposure to NGF. Experimental Approach Withdrawal thresholds to heat, von Frey hairs and pressure were measured in mice before and after systemic administration of NGF. Changes in intracellular Ca2+ concentration were measured by ratiometric imaging with Fura‐2 in cultured DRG and trigeminal ganglia (TG) neurons during perfusion of TRPV4 agonists. Key Results Administration of NGF caused a significant sensitization to heat and von Frey stimuli in TRPV4 +/+ and –/– mice, but only TRPV4 +/+ mice showed sensitization to noxious pressure. 4αPDD stimulated a dose‐dependent increase in [Ca2+]i in neurons from +/+ and –/– mice, with the proportion of responding neurons and magnitude of increase unaffected by the genotype. In contrast, the selective TRPV4 agonist GSK1016790A failed to stimulate an increase in intracellular Ca2+ in cultured neurons. Responses to 4αPDD were unaffected by pretreatment with NGF. Conclusions and Implications TRPV4 contributes to mechanosensation in vivo, but there is little evidence for functional TRPV4 in cultured DRG and TG neurons. We conclude that 4αPDD activates these neurons independently of TRPV4, so it is not appropriate to refer to 4αPDD as a selective TRPV4 agonist.